Extreme value analysis of streamflow time series in the last half century in the Poyang Lake Basin, China - Peng TIAN; Guang-ju ZHAO; Jing LI; Kun TIAN (Water Science and Engineering, 2011)
Climate change and intensive human activities are threatening water resource systems throughout the world. The water system in Poyang Lake Basin is especially vulnerable to these impacts due to the human influences, climate changes and interaction between Yangtze River and Poyang Lake. In recent decades, more and more studies have focused on the extreme hydro-meteorological events. By use of observed records of Poyang Lake Basin for nearly 50 years, the occurrence, frequency and changing trends of extreme streamflow indices (including annual maximum flow, peak-over-threshold flow indices and low flows) are analyzed for ten hydrological stations. Results indicate that most annual maximum flows occurred from April to June, highly attributed to the Southeast Asian summer monsoons, whereas the annual minimum flow concentrated between January and February. As for the low flow indices, (Annual minimum flow, Annual minimum 7-day flow, and Annual minimum 30-day flow) a significant increasing trend was detected in most parts of the Poyang Lake Basin. The trends illustrate the potential effects of climate change and human activities on the hydrological cycle over Poyang Lake Basin.